Quantifying the Effects of the Inclusion and Segregation of Contracts for Difference in Australian Equity Markets - Corbet, Shaen; Twomey, Cian (International Journal of Economics and Financial Issues, 2014)
This study examines the effects that Contracts for Difference (CFDs) have had on the Australian equity market, either as an accelerant for mispricing, or as a source of increased market functionality through the addition of a new tradable product and increased liquidity. The Australian Securities Exchange (ASX) made the decision to segregate CFDs to a separate ring-fenced exchange in November 2007. This study uses EGARCH techniques to test for the effects of CFDs on return volatility at the time of CFD inclusion and segregation in Australian equity markets at the index and equity-specific level. A fully worked explanation and example of a CFD-influenced ‘overhang’ is also provided. The results provide evidence that cannot reject the presence of ‘overhangs’ in Australian equity markets. Keywords: Contracts for Difference; EGARCH; equity markets; volatility. JEL Classifications: G12; G15